Effectiveness of training program in RISDA Melaka / Mohd Fazley Ab Ghafar - Ab Ghafar, Mohd Fazley (Faculty of Business and Management, 2009)
This study is designed to observe the effectiveness of training program in Risda Melaka. This dimension will be used to identify effectiveness towards RISDA Training program in Melaka., the methods used in the case study are personal interview and questionnaire. This method used to identify the effectiveness towards RISDA Training program in Melaka to the smallholder. Researcher also used secondary data such as journals, references books, and internal data. All the data is obtained from RISDA Melaka training program in 2008. Researcher also used probability sampling technique which is the simple random sampling to gain information regarding this research. Researcher also used the close-ended question to obtain the information .50 questionnaire was given to respondent to answer the questionnaire. The result on effectiveness towards RISDA Training program in Melaka. It will suggest whether RISDA Melaka may need changes or improve their training program provided to its customer in order to be able to provide better training program to the smallholder.